EXPERIENCE IN STUDENT PARTICIPATION IN THE MEANINGFUL INFORMATION PROJECTS BY THE EXAMPLE OF DEVELOPMENT OF MULTIMEDIA APPLICATION «COPPER ART MOLDING OF XVI–XX CENTURES FROM THE COLLECTION OF THE NATIONAL MUSEUM OF THE KOMI REPUBLIC» - Аlexandra S. Bolshakova; Igor M. Vinogradov; Yury V. Golchevskiy (Открытое образование (Москва))
The paper presents the example of student participation in the meaningful information projects in the Komi Republic, the information technologies applying in culture, in particular, the creation of multimedia applications for distribution on CDs or other digital carriers. The project of creation the multimedia application "Copper art molding: crosses, icons, folding XVI – XX centuries from the National Museum of the Komi Republic collection" is described.